Thomas Wright Vaughan correspondence - Vaughan, Thomas Wright, 1774-1859.
Letter from Vaughan to Mr. Stockdale, a London bookseller, relating to affairs in Sicily.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Sicily (Italy) -- Description and travel